Mobile Devices in Education 2020
DOI: 10.4018/978-1-7998-1757-4.ch021
|View full text |Cite
|
Sign up to set email alerts
|

University Students' Perceptions of Personal Mobile Devices in the Classroom and Policies

Abstract: This chapter discussed the results of a study that explored students' perceptions of personal mobile devices in the classroom and suggestions for policies. Thirty-four students enrolled in two undergraduate courses taught at a Brazilian higher education institution took part in the study. Data collection consisted of a survey and focus group interview. Quantitative data suggested an overall tendency to rare use of the devices for content and non-content activities. Qualitative results, however, showed that stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…smartphones and iPads, can be a useful learning tool to increase interaction during the lectures' time (Aldiab, Chowdhury, Kootsookos, Alam, & Allhibi, 2019;McClean & Crowe, 2017). However, the use of such technology needs an adoption of appropriate pedagogies (Emery, 2012;Santos & Bocheco, 2017). Furthermore, students need to have more opportunities to collaborate and react as active agents in the learning settings (Daniela, Visvizi, Gutiérrez-Braojos, & Lytras, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…smartphones and iPads, can be a useful learning tool to increase interaction during the lectures' time (Aldiab, Chowdhury, Kootsookos, Alam, & Allhibi, 2019;McClean & Crowe, 2017). However, the use of such technology needs an adoption of appropriate pedagogies (Emery, 2012;Santos & Bocheco, 2017). Furthermore, students need to have more opportunities to collaborate and react as active agents in the learning settings (Daniela, Visvizi, Gutiérrez-Braojos, & Lytras, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that BYOD could disrupt students' learning because students sometimes use their devices to perform non-content related activities. For example, they can read/send/replay text messages or browse the non-relevant websites (Santos & Bocheco, 2017). Another obstacle is that some students may not be able to bring a high-quality device to the classroom (Kay & Schellenberg, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review addressed many of the long-standing misgivings about BYOD adoption. However, as the KSA works towards accomplishing the objectives of the Saudi Vision 2030 Plan, which includes reaching the technical readiness outlined by the IMD, these reservations remain a major obstacle to BYOD adoption in the country [70][71][72]. According to most of the respondents of this present study, this was due to a lack of BYOD frameworks, regulations, and policies on the execution of administrative tasks and working on personal devices in the workplace.…”
Section: Discussionmentioning
confidence: 94%